PENGARUH INJEKSI HORMON HUMAN CORIONIC GONADOTROPIN (hCG) TERHADAP PERKEMBANGAN GONAD IKAN KEBALI (Oesteochilus Schlegeli Blkr) - Eko Dewantoro; Purnamawati .; Rachimi .; Rudi Alfian; Akhmad Fadil (UNIVERSITAS MUHAMMADIYAH PONTIANAK, 2020)
The purpose of this study is to determine the optimal dose of hCG homrone on gonad maturation of parent prospective of kebali fish through regular injection. The research was carried out in Aquatic Environment Laboratory of Fisheries and Marine Science Faculty, Universitas Muhammadiyah Pontianak and Floating Net Cage (KJA) in Kelurahan Parit Mayor of Pontianak, that was carried out for 60 days. The expermental design used was a randomized block design (RBD) consisting of 3 groups and each group consisted of 6 treatments. As a treatment is hCG hormone was injected periodically from doses of 0 to 250 IU/kg of fish. Variables observed were Gonad Maturity Level (TKG), Gonado Somatic Index (GSI), Hepato Somatic Index (HSI), fecundity and eggs diameter. The results showed a dose of 150 until 250 IU/kg of fish can reach TKG IV with a greater proportion, a dose of 100 IU/kg of fish can reach TKG III, while the doses below only reach TKG I and II. The average value of HSI in each treatment was 0.74-1.57% and the GSI value is 1.64-4.51% with the highest HSI and GSI achieved at hCG injection with a dose of 150 IU/kg of fish that was with an index value of 1.57% and 4.51% respectively. The average of fish fecundity at hCG hormone doses of 100–150 IU/kg of fish ranged from 11,592–18,059 eggs, with the highest fecundity (18,059 eggs) achieved at the hormone dose of 250 IU/kg of fish. The range of eggs diameter produced after gonad maturation were 0.07–0.37 mm, hCG injection treatments of 150–250 IU/kg generally produces eggs that are 0.24–0.31 mm in size, and the injection dose was 250 IU/kg in part large eggs have a diameter of 0.28–0.31 mm. Water quality during the study was quite supportive for the maturation process of the ovary. Periodic injection of hCG hormone at a dose of 150 IU / kg of fish is the best dose for gonad maturation of kebali fish.